Interpersonal liking, cultural belonging, and heritage language: exploring the role of metaperception in interaction between heritage speakers of Vietnamese - Le, Thao-Nguyen Nina; Trofimovich, Pavel; McDonough, Kim; Sato, Masatoshi (Frontiers in Communication, 2024)
Metaperceptions (or the impressions people believe to make on others) are a potential source of misconception in conversations involving members of the same ethnic community. We investigated whether speakers’ tendency to underestimate how they are perceived by others has consequences for future interaction. In this quantitative study, we paired 46 previously unacquainted speakers of Vietnamese as a heritage language (23 second-generation speakers, 23 recent immigrants) for two conversations. The speakers in each pair, recruited through convenience sampling, were similar in age (all young adults, with a range of 18–39 years). Each pair included one second-generation speaker born in Canada, age-matched with one immigrant, with a balanced distribution of speakers’ gender (eight pairs of women, seven pairs of men, and eight mixed pairs). After each conversation, the speakers used a 100-point scale to assess each other’s interpersonal liking, cultural belonging, and heritage language ability, provided their metaperceptions for their partner’s ratings, and assessed their willingness to engage in future interaction. Results of statistical comparisons (ANOVAs, correlations) indicated that all speakers underestimated how their partner perceived their interpersonal liking and heritage language (but not cultural belonging), but all ratings improved over time. However, only Vietnam-born speakers seemed to factor their perceived cultural belonging into their willingness to engage in future communication. We discuss implications of these findings for intragroup cohesion and contact.